Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/etm.2016.3469
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging DTI-FT study on schizophrenic patients with typical negative first symptoms

Abstract: Magnetic resonance imaging (MRI) with diffusion-tensor imaging (DTI) together with a white matter fiber tracking (FT) technique was used to assess different brain white matter structures and functionalities in schizophrenic patients with typical first negative symptoms. In total, 30 schizophrenic patients with typical first negative symptoms, comprising an observation group were paired 1:1 according to gender, age, right-handedness, and education, with 30 healthy individuals in a control group. Individuals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Studies reported association between bilateral cortical thickness reductions in the temporal lobe and executive dysfunction in schizophrenia (Hartberg et al, 2010), as well as an association between white matter volume reductions in the temporal lobe and verbal memory, attention, problem solving, and working memory dysfunctions in a follow-up study of early-onset schizophrenia (Andreasen et al, 2011). The current results suggest that the disconnection be- the DTI whole-brain analysis in schizophrenia have been repeatedly reported in the rostrum (Ellison-Wright et al, 2014;Fujino et al, 2014;Gu et al, 2016;Hummer et al, 2016;Kochunov et al, 2014;Kong et al, 2011;Lener et al, 2015;Melicher et al, 2015;Pérez-Iglesias et al, 2010;Pomarol-Clotet et al, 2010;Roalf et al, 2013;Spalletta et al, 2015;Zhang et al, 2014Zhang et al, , 2016, body (Fujino et al, 2014;Melicher et al, 2015;Pérez-Iglesias et al, 2010;Roalf et al, 2013;Zhang et al, 2014Zhang et al, , 2016, and splenium of the CC (Cheung et al, 2008;Ellison-Wright et al, 2014;Fujino et al, 2014;Gasparotti et al, 2009;Melicher et al, 2015;Zhang et al, 2014). A meta-analysis of 22 studies found decreased FA values in the genu and splenium of CC in schizophrenia (Zhuo, Liu, Wang, Tian, & Tang, 2016).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Studies reported association between bilateral cortical thickness reductions in the temporal lobe and executive dysfunction in schizophrenia (Hartberg et al, 2010), as well as an association between white matter volume reductions in the temporal lobe and verbal memory, attention, problem solving, and working memory dysfunctions in a follow-up study of early-onset schizophrenia (Andreasen et al, 2011). The current results suggest that the disconnection be- the DTI whole-brain analysis in schizophrenia have been repeatedly reported in the rostrum (Ellison-Wright et al, 2014;Fujino et al, 2014;Gu et al, 2016;Hummer et al, 2016;Kochunov et al, 2014;Kong et al, 2011;Lener et al, 2015;Melicher et al, 2015;Pérez-Iglesias et al, 2010;Pomarol-Clotet et al, 2010;Roalf et al, 2013;Spalletta et al, 2015;Zhang et al, 2014Zhang et al, , 2016, body (Fujino et al, 2014;Melicher et al, 2015;Pérez-Iglesias et al, 2010;Roalf et al, 2013;Zhang et al, 2014Zhang et al, , 2016, and splenium of the CC (Cheung et al, 2008;Ellison-Wright et al, 2014;Fujino et al, 2014;Gasparotti et al, 2009;Melicher et al, 2015;Zhang et al, 2014). A meta-analysis of 22 studies found decreased FA values in the genu and splenium of CC in schizophrenia (Zhuo, Liu, Wang, Tian, & Tang, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that WM tracts in the temporal lobe may affect in schizophrenia, with the disconnectivity of the gray matter regions which they link. Decreased FA values of the CC on the DTI whole‐brain analysis in schizophrenia have been repeatedly reported in the rostrum (Ellison‐Wright et al, ; Fujino et al, ; Gu et al, ; Hummer et al, ; Kochunov et al, ; Kong et al, ; Lener et al, ; Melicher et al, ; Pérez‐Iglesias et al, ; Pomarol‐Clotet et al, ; Roalf et al, ; Spalletta et al, ; Zhang et al, , ), body (Fujino et al, ; Melicher et al, ; Pérez‐Iglesias et al, ; Roalf et al, ; Zhang et al, , ), and splenium of the CC (Cheung et al, ; Ellison‐Wright et al, ; Fujino et al, ; Gasparotti et al, ; Melicher et al, ; Zhang et al, ). A meta‐analysis of 22 studies found decreased FA values in the genu and splenium of CC in schizophrenia (Zhuo, Liu, Wang, Tian, & Tang, ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, after Holm–Bonferroni correction, these correlations became less strong [ 41 , 82 ]. In contrast, there are reports of negative correlations of FA in the CC with positive symptoms [ 83 ] and negative symptoms [ 59 , 76 , 83 , 84 ]. This ambiguity is exacerbated by reports that did not find any links between psychopathology and diffusion parameters [ 85 ].…”
Section: Discussionmentioning
confidence: 99%